Application Of Some Methods For Price Trends Re-search In Real Estate Market (Research Bulletins of the Faculty of Economic Sciences, 2017)
Main aim of this article is to attempt to apply selected methods to study price trends, short-term forecasts of real estate prices. The main research problem was formulated as a question: What are the short-term forecasts of prices on the real estate market residential-tions in Koszalin? Assumed a relatively fixed price trend on the real estate market in Koszalin. To verify the assumptions the method of Brown's method of moving averages were used. The use of two different methods to forecast prices for the next months helped to show how much depends on the chosen method and showed the difficulties faced in predicting what will happen in the coming months.
Keywords: forecast; method; price; real estate